2018
DOI: 10.1111/gcb.14464
|View full text |Cite
|
Sign up to set email alerts
|

Uneven winter snow influence on tree growth across temperate China

Abstract: Winter snow is an important driver of tree growth in regions where growing‐season precipitation is limited. However, observational evidence of this influence at larger spatial scales and across diverse bioclimatic regions is lacking. Here, we investigated the interannual effects of winter (here defined as previous October to current February) snow depth on tree growth across temperate China over the period of 1961–2015, using a regional network of tree ring records, in situ daily snow depth observations, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 65 publications
3
33
0
Order By: Relevance
“…Climate change effects on vegetation have been documented at annual and seasonal scales, with the most research directed at evaluating the effects of climate in summer months. However, climate warming is more pronounced in winter than summer at locations in the mid‐ to high‐latitudes (Xia et al, ), where changing winter precipitation patterns (spatial and temporal variability, type; Wu et al, ), extreme cold events (magnitude and frequency; Kodra, Steinhaeuser, & Ganguly, ) and temperature (variability in extremes and mean) can independently and collectively influence patterns of vegetation growth and distribution, especially in temperate mixed‐wood forests (Kreyling, ; Kreyling & Henry, ). To better identify the effects of these climatic changes on forest productivity, spatially explicit estimations of tree growth (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change effects on vegetation have been documented at annual and seasonal scales, with the most research directed at evaluating the effects of climate in summer months. However, climate warming is more pronounced in winter than summer at locations in the mid‐ to high‐latitudes (Xia et al, ), where changing winter precipitation patterns (spatial and temporal variability, type; Wu et al, ), extreme cold events (magnitude and frequency; Kodra, Steinhaeuser, & Ganguly, ) and temperature (variability in extremes and mean) can independently and collectively influence patterns of vegetation growth and distribution, especially in temperate mixed‐wood forests (Kreyling, ; Kreyling & Henry, ). To better identify the effects of these climatic changes on forest productivity, spatially explicit estimations of tree growth (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in this study area has shown that soil temperature played a key role for the initiation of radial growth for both larch and spruce [8,44]. The threshold value of soil temperature for larch xylogenesis was above 0 • C as frozen soil will inhibit water uptake and activity in root systems [45]. Moreover, the correlation coefficients indicated that the growing degree days of soil temperature (GDD s ) better explained the shoot growth and stem growth, whereas the daily soil temperature was better for needle growth in larch (Table 4).…”
Section: Environmental Effect On Growthmentioning
confidence: 88%
“…In humid regions, water availability was likely not the main limiting factor for NDVI; instead, variations in temperature, solar radiation as well as CO 2 concentration interactively controlled tree growth [46,50] (Figure 5; Figure S2). Tree growth in drier regions tends to be increasingly affected by early growing season water availability and winter snow exerts important effects on tree growth, with contributions ranging from 2% to 23% across diverse climate zones over northeastern China [25]. More importantly, the water-limited regions are becoming drier accompanied due to rapid climate warming [51], which exerts intensified drought stress on tree growth and could further trigger tree growth decline ( Figure 5).…”
Section: Divergent Tree Growth Trends In Different Seasonsmentioning
confidence: 99%
“…Therefore, increasing efforts have been devoted to the understanding of forest growth and its response to the changing climate [21][22][23]. Studies based on both satellite observations and in situ forest investigation have revealed that the temperate forest is particularly sensitive to climate change in northeastern China [17,22,24,25]. Past studies mainly focused on the annual tree growth trend and its drivers [8,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%